A review of the book Kasinomic Revolution: The rise of African Informal Economies. Written by GG Alcock - Monareng, Luther Lebogang (South African Journal of Occupational Therapy, 2023)
The author restates the need for Afrocentric systems such as building modern villages to accommodate Africa’s uniqueness. He condemns the practices of marginalising the informal economy as it contributes to countries’ Gross Domestic Production (GDP). GG alludes that jobs are now beyond the conventional “8 to 5 job with a payslip” and that communities of ordinary people should not be treated as “breeding grounds for employees”. Moreover, he highlights that the colonial and Western systems are unjust to the masses in developing countries. Africa needs no “bicycle lanes but hawker lanes” where they can trade closer to their clientele without being fearful of municipalities chasing them.